Relative contribution of cationic surfactant and counter-anion to a liquid film tension - Phan, Chi; Haseeb, M. (2020)
A model was developed to predict the bubble deformation in the presence of a charged surface. The model was successfully verified with a bubble containing a cationic surfactant, cetyltrimethylammonium bromide. The modelling results revealed that the film tension linearly increased with the distance from the charged surface, due to the electrostatic repulsion of the anions. More importantly, the analysis demonstrated that hydrated Br− increased film tension, whereas surfactant molecules reduced film tension. The anion's increment was estimated at ~14% of the surfactant's reduction. The results verified the contrasting influences of surfactant and its counter-ions on the tension of the air/liquid interfacial layer.